Peran Krusial Pengelolaan Dan Perencanaan Sumber Daya Manusia Dalam Mencapai Kemajuan Organisasi - Zalsabillah, Imelda; Rahayu , Angelia Tri; Butar , Melati Butar (Utami Publisher, 2025)
Human resources are valuable assets for an organization, so effective HR management is essential for organizations to stay ahead in a dynamic business environment. Quality, productive, and highly committed employees enable a company to adapt to change and achieve its goals. Job satisfaction must be a priority to retain the best talent. Job analysis and job design play a key role; analysis helps identify task needs and qualifications, while design motivates and improves employee performance. With optimal HR management, organizations can design development, increase productivity, and deal with change flexibly, supporting business growth and sustainability.